Peningkatan Kesehatan dan Kekebalan Tubuh Lansia pada Masa Pandemi Covid 19 Melalui Gerakan 3M : Mencuci Tangan, Memakai Masker dan Meminum Jamu - Sulistyawati, Wiwin; Etika, Arif Nurma; Yunalia, Endang Mei; Suharto, Idola Perdana Sulistyoning; Nurseskasatmata, Satria Eureka (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2021)
The increasing number of Covid 19 sufferers makes us have to make solution steps to avoid Covid 19. The elderly are a vulnerable group to contracting this virus. There are degenerative diseases that appear in the elderly, such as diabetes and hypertension, which will worsen the condition of the elderly. The application of 3M (washing hands, wearing masks, and drinking herbal medicine) can improve the health and immunity of the elderly. This community service activity carried in three stages: the preparation stage (coordinating with partners), the implementation stage (conducting education on proper handwashing, wearing masks, conducting herbal medicine training), and the evaluation stage. This community service activity was held at the MK 2 posyandu, Tamanan sub-district, Kediri City. This activity is the distribution of hands-on aid, masks, and herbal medicine, and an increase in public knowledge about 3M. The application of washing hands, wearing masks, and drinking herbal medicine can be a solution to prevent transmission of Covid 19 to the elderly.